Inhibitory Processes for Critical Situations – The Role of n−2 Task Repetition Costs in Human Multitasking Situations - Gade, Miriam; Koch, Iring (Frontiers in Physiology, 2012)
The human cognitive system is equipped with various processes for dealing with everyday challenges. One of such processes is the inhibition of currently irrelevant goals or mental task sets, which can be seen as a response to the critical event of information overflow in the cognitive system and the cognitive system’s inability to keep track of ongoing demands. In two experiments, we investigate the flexibility of the inhibitory process by inserting rare non-critical events (25% of all trials), operationalized as univalent stimuli (i.e., unambiguous stimuli that call for only one specific task in a multitasking context), and by introducing the possibility to prepare for an upcoming task (Experiment 2). We found that the inhibitory process is not influenced by a cue informing subjects about the upcoming occurrence of a univalent stimulus. However, the introduction of univalent stimuli allowed preparatory processes to modify the impact of the inhibitory process. Therefore, our results suggest that inhibitory processes are engaged in a rather global manner, not taking into account variations in stimulus valence, which we took as operationalization of critical, conflict-inducing events in the ongoing stream of information processing. However, rare uncritical events, such as univalent stimuli that do not cause conflict and interference in the processing stream, appear to alter the way the cognitive system can take advantage of preparatory processes.